Trajetória dos assentamentos rurais financiados pelo crédito fundiário no Estado do Rio Grande do Norte: uma análise da experiência do assentamento da Fazenda Paz no município de Maxaranguape/RN - Fernandes, Vinícius Rodrigues Vieira (2014)
The market-assisted land reform (RAAM) has been constituted as an alternative of agrarian reform funded by the Programa Nacional do Crédito Fundiário (PNCF). It is a policy of acquisition, distribution and use of Earth ideologically disseminated and funded by the World Bank in the context of productive insertion of landless workers. Accordingly, this study seeks to analyze the trajectory of rural settlements financed by this policy, seeking to understand what factors promote or limit the process of rural development of those settlements. To do so, take as a reference case study of the Assentamento da Fazenda Paz, in the municipality of Maxaranguape in the State of Rio Grande do Norte. From the methodological point of view, bibliographical and documentary research were used, in addition to visits to the settlement and semi-structured interviews with the settlers, trade union leaders, consultants and technicians linked to the project. Assuming the reports of respondents, initially constructs the hypothesis that informal and formal institutions present in the Assentamento da Fazenda Paz were unable to effectively coordinate the actions of the agents. The results obtained showed the existence of a very complex undertaking, with a total area of 607 hectares and 80 families settled, endowed with good quality water and irrigation infrastructure, with assets of approximately R$ 5 million reais. Experience experienced by the settlers understood the development of complex systems of production and marketing of fruits and vegetables, with an emphasis on the cultivation of papaya in an area of 45 hectares based on modern irrigation system and extensive use of technology. Collective management of production, marketing, revenue and costs stood out as a major challenge for the settlers and their representative organisations, i.e. the Community Association and the cooperative. From this observation it was possible to identify two moments on the trajectory of the project: the first, between 2007-2011, considered by respondents as successful, in which the integration of public policies and abundant input of revenue from the commercialization of the fruits da Paz, mainly through the sale of papaya and pineapple in national and international markets, allowed an average remuneration of R$ 800.00 reais to R$ 1,000 reais seated/monthIn addition to the production of vegetables and other types of products for sale and consumption; the second, from 2012, characterized as a failure, due to the discontinuity of the cultivation, production and marketing of fruits based on the collective bargaining model deployed. Important factors explain the discontinuity of the project, including the model of agriculture implemented, difficulties related to the management of production, marketing and finance the venture, in addition to the breach of trust between the Board of the cooperative and the associates and the distancing of the governmental organizations more directly responsible for the project. It is therefore concluded that we must to rethink rural development as a multidimensional phenomenon, requiring a broad engagement between State and society under the foundations of a territorial development contract